Whey Protein Isolate and β-Lactoglobulin-Modified Alginate Hydrogel Scaffolds Enhance Cell Proliferation for Cultivated Meat Applications - Irfan Tahir; Christopher Foley; Rachael Floreani (Foods, 2025)
Innovative changes to our current food system are needed, and one solution is cultivated meat, which uses modern engineering, materials science, and biotechnology to produce animal protein. This article highlights the advantages of incorporating whey protein isolate (WPI) and β-lactoglobulin (β-LG) into hydrogel networks to aid cell growth on cultivated meat scaffolds. The protein and polysaccharide (i.e., alginate) components of the scaffolds are food-grade and generally regarded as safe ingredients, enabling the transition to more food-safe, edible, and nutritious scaffolds. The impact of WPI and varying properties on cell performance was evaluated; alginate concentration and the addition of proteins into the hydrogels significantly altered their stiffness and strength. The results of this study demonstrate the innocuous nature of novel scaffolds and reveal enhanced cell proliferation on WPI and β-LG-modified groups compared to standard biomaterial controls. This work serves as a stepping stone for more comprehensive analyses of WPI, β-LG, and alginate scaffolds for use in cultivated meat research and production.